OSTEOSYNTHESIS OF PROXIMAL HUMERAL END FRACTURES WITH FIXED-ANGLE PLATE AND LOCKING SCREWS: TECHNIQUE AND RESULTS - Cohen, Marcio (Rev Bras Ortop, 2015)
Describe the results of proximal humeral fractures surgically treated with the Philos locking plate system. Method: Between March 2003 and October 2004 we prospectively reviewed 24 of 26 patients with proximal humerus fractures treated with a Philos plate. The mean follow-up time was 12 months and the mean age of patients was 57 years. Six patients had four-part proximal humerus fractures, 11 patients had three-part proximal humerus fractures, and nine patients had two-part proximal humerus fractures. Clinical evaluation was performed using the University of California at Los Angeles (UCLA) criteria. Results: The mean UCLA score was 30 points (17-34). All fractures showed union. Three patients showed fracture union at varus position. The mean UCLA score for these patients was 27 points. Conclusion: Osteosynthesis with Philos plate provides a stable fixation method with good functional outcome.